Perancangan Antarmuka Sistem Peringatan Dini Banjir Menggunakan Web Thing Speak sebagai Basis Data dan Notifikasi Pesan melalui Aplikasi WhatsApp - Nabil Sarmada; Erlangga Alman Rahardjo; Lutfi Firmandany; Khilda Afifah; Bandiyah Sri Aprillia (Faculty of Engineering, Universitas Serambi Mekkah, 2024)
Flooding is one of the natural disasters that frequently occur in Indonesia, especially in Bandung Regency, which is often affected by flooding due to river basins that cannot accommodate excess water. To address this problem, an Internet of Things (IoT)-based flood early warning system (FEWS) has been developed that can monitor river water levels and provide early notification to the public via the WhatsApp application. This study aims to design and test a user interface integrated with the FEWS system using ThingSpeak as the database and WhatsApp as the notification application. The methods used include data collection, requirements analysis, design, implementation, and system testing. The test results show that ThingSpeak is able to upload water level data in real time with an average delay of 11.5 seconds, and WhatsApp successfully sends water level category notifications to users in a timely manner. In conclusion, the developed system successfully provides accurate information and appropriate notifications to help the public take early evacuation steps during floods.